CANCER: A MOLECULAR CURSE? - Piero, Ngugi M.; Joan, Njagi M. (International Journal of Current Pharmaceutical Research, 2015)
Cancer is one of the most common causes of death, taking over 7 million lives each year globally. The global incidence is remarkably rising. Massive investments in research are also on the rise to unravel the genetic and molecular basis of cancer as a prerequisite to design of more effective treatment strategies. This review explores causes of cancer, its molecular basis and the treatment strategies. Future perspectives regarding research on cancer and envisaged milestones of management and/or treatment interventions are also explored.